The Prototype of Orchid Plantation Monitoring and Control System Based on Internet of Things - Dania Eridani (Journal of Telematics and Informatics, 2018)
Orchids are ornamental plant that live in various kind of temperature depending on its type, but mostly in a cool environment.  An orchid that planted in a soil media cannot live in the condition that is too wet or too dry. To keep orchid plant in good condition, a monitoring of the plant’s condition is necessary. Internet of Things (IoT) is a technology that can enable communication between one components to others via internet. By using IoT, the control and monitor system of the orchid plantation system is able to be built wirelessly in a long distance. The system built using DHT22 as temperature sensor. YL69 used as humidity sensor and Arduino Mega 2560 used as the main controller. ESP8266 used as the communication board sothat the system can access the Blynk server. 16x2 LCD is used as the display and relay is put to control the connection of water pump and the fan. The result of this research is that the monitoring system is able to watch the data delivered by the sensor via internet. The control system also fully able trigger the water pump and the fan